2020
DOI: 10.1111/jocn.15405
|View full text |Cite
|
Sign up to set email alerts
|

Parental readiness for hospital discharge as a mediator between quality of discharge teaching and parental self‐efficacy in parents of preterm infants

Abstract: Aims and objectives To examine the extent to which parental readiness for hospital discharge mediates the relationship between quality of discharge teaching and parental self‐efficacy in parents of preterm infants. Background Parental readiness for hospital discharge and self‐efficacy should be considered to establish whether preterm infants and their families are prepared for the discharge. High‐quality discharge teaching could facilitate a smooth discharge transition. However, little is known about how quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
0
15
1
Order By: Relevance
“…Interestingly, for the Readiness for Hospital Discharge Scale, the item median score was 8.82, and 98.8% of the participants stated they were ready for discharge, which was higher than that in previous studies of other populations [ 24 , 25 , 36 , 37 ]. One reason might be the relatively young age of our participants.…”
Section: Discussioncontrasting
confidence: 66%
“…Interestingly, for the Readiness for Hospital Discharge Scale, the item median score was 8.82, and 98.8% of the participants stated they were ready for discharge, which was higher than that in previous studies of other populations [ 24 , 25 , 36 , 37 ]. One reason might be the relatively young age of our participants.…”
Section: Discussioncontrasting
confidence: 66%
“…Construct validity has been confirmed by a factor analysis of four of the subscales and by comparing parents who were ready and not ready for their infants' discharges 2 . Cronbach's alpha has been reported to be between 0.83 and 0.92 in different populations, including the parents of hospitalised preterm infants 2,6,8,23 …”
Section: Methodsmentioning
confidence: 91%
“…6 This scale was developed by Weiss and Piacentine 2 and has been used with parents in neonatology settings. 8 The scale comprises 29 items, divided into five subscales: the parent's personal status, the infant's personal status, knowledge, coping ability and the emotional, technical and medical support that parents expect after discharge. 6 Each item is rated on a scale from 1 to 10 and the total score is the sum of all the items.…”
Section: Methodsmentioning
confidence: 99%
“…A study from China found the quality of teaching and content of information provided to parents during discharge to be an important determinant of parents’ readiness [ 25 ]. Similar to our study, parents’ frustration due to inconsistent and conflicting information from healthcare providers was a theme that emerged from other research [ 21 ].…”
Section: Discussionmentioning
confidence: 99%